Implementation of RPWD Act in Karnataka: Accessibility, Education and Employment Policy Review - Kumar Dash, Prasanta; Choubey, Srashti (Journal of Social Science and Humanities, 2025)
This paper critically examines of the enactment of the Rights of Persons with Disabilities Act, 2016, in Karnataka, through a specific emphasis on accessibility, education and employment. The research is grounded in the findings of the Comptroller and Auditor General Report No.2 of 2024, which identifies systemic challenges and gaps that impede the effective realization of the rights of persons with disabilities in the state. The study uncovers significant deficiencies in infrastructure accessibility, inclusive education and employment opportunities. Despite the existence of legal mandates and policy frameworks under the RPwD Act, the state has faced considerable obstacles, such as insufficient resource allocation, weak stakeholder coordination and low public awareness. In the area of accessibility, persistent issues include non - compliance with universal design principles and the absence of accessible public spaces. In education, the research underscores the necessity for trained personnel, accessible learning materials and inclusive curricula. Employment challenges are linked to the low participation of PwDs in the workforce, further exacerbated by limited enforcement of reservation policies and inadequate workplace accommodations. To address these challenges, the paper introduces a policy evaluation framework that integrates international best practices, particularly those aligned with the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD). The proposed framework advocates for inter - departmental collaboration, community involvement and the adoption of technology - driven solutions to improve accessibility and promote inclusion. The paper concludes with recommendations for targeted policy interventions, capacity - building initiatives and effective monitoring mechanisms. By narrowing the gap between policy and practice, Karnataka can develop the quality of life then prospects for persons with disabilities, ensuring their full and equal involvement in society.